Overgrowth of the lower limb after treatment of developmental dys- plasia of the hip: incidence and risk factors in 101 children with a mean follow-up of 15 years - Shin, Chang Ho; Yoon , Chan; Kim, Dong Ook; Park , Moon Seok; Yoo, Won Joon; Chung, Chin Youb; Choi, In Ho; Cho , Tae-Joon (Acta Orthopaedica, 2019)
Background and purpose — There are few studies on overgrowth of the affected limb after treatment of developmental dysplasia of the hip (DDH). We investigated the incidence of overgrowth and its risk factors in DDH patients. Patients and methods — 101 patients were included in this study. Overgrowth was defined by 2 criteria: when the height of the femoral head of the affected side was higher than that of the contralateral side by more than 10 mm, or by more than 15 mm. The potential risk factors of distinct overgrowth were retrospectively examined using multivariable analysis. Results — When overgrowth was defined as femoral head height difference (FHHD) > 10 mm, its incidence was 44%, and only femoral osteotomy was identified as a significant risk factor with a relative risk (RR) of 1.6 (95% confidence interval [CI] 1.0–2.5). When overgrowth was defined as FHHD > 15 mm, its incidence was 23%, and femoral osteotomy was identified as the only significant risk factor with an RR of 2.3 (CI 1.2–4.5). Overgrowth developed more frequently in patients who underwent femoral osteotomy at the age of 2 to 4 years (87%) than in the others (46%) (p = 0.04). Interpretation — Overgrowth of the affected limb is common in DDH patients. Patients who underwent femoral osteotomy, especially at the age of 2 to 4 years, may require careful follow-up because of the substantial risk for overgrowth.